Least square application on frequency weighted model reduction technique - Sahlan, Shafishuhaza; Shikh Maidin, Mashitah; Abdul Wahab, Norhaliza (IEEE, 2011)
In this paper, we present new results on frequency weighted balanced truncation technique based on vec and Kronecker Product. This technique is applied to single-sided case and an extension to double-sided case is also presented. Numerical example with comparisons to other techniques is also presented.